2019
DOI: 10.3390/su11185133
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Carbon Footprint of Dry Bulk Shipping in the EU: An Early Assessment of the MRV Regulation

Abstract: Aiming at reducing CO2 emissions from shipping at the EU level, a system for monitoring, reporting, and verification (MRV) of CO2 emissions of ships was introduced in 2015 with the so-called ‘MRV Regulation’. Its stated objective was to produce accurate information on the CO2 emissions of large ships using EU ports and to incentivize energy efficiency improvements by making this information publicly available. On 1 July 2019, the European Commission published the relevant data for 10,880 ships that called at E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…In line with some of the literature on transparency (i.e. Mol, 2010;Gupta and Mason 2014, Bullock 2014, Gardner et al 2019, we have found that GHG data collection through the MRV is unlikely to lead to substantial fuel savings per se (see also Psaraftis and Woodall, 2019;Lonsdale et al, 2019;and Panagakos 2019). The MRV aims at both disclosure-and education-based transparency as it focuses on both informing the public and value chain actors and on educating shipowners and managers in an attempt to reduce fuel consumption.…”
Section: Discussionsupporting
confidence: 88%
“…In line with some of the literature on transparency (i.e. Mol, 2010;Gupta and Mason 2014, Bullock 2014, Gardner et al 2019, we have found that GHG data collection through the MRV is unlikely to lead to substantial fuel savings per se (see also Psaraftis and Woodall, 2019;Lonsdale et al, 2019;and Panagakos 2019). The MRV aims at both disclosure-and education-based transparency as it focuses on both informing the public and value chain actors and on educating shipowners and managers in an attempt to reduce fuel consumption.…”
Section: Discussionsupporting
confidence: 88%
“…Table 1. Some CIIs after [2,7,8]. Proxy of transport work τ(L, x C ) and its argument x C are also provided.…”
Section: Introductionmentioning
confidence: 99%
“…Although the calculation of the EEOI is considered as the primary monitoring tool-as per the 2016 Guidelines for the development of a Ship Energy Efficiency Management Plant (SEEMP)-EEOI-related data are not reported to the IMO and could be difficult to verify. Various other reservations are also reported on the reliability of EEOI as an operational index (see [25,37,38] among others). By contrast, the deadweight of a vessel is known and is reported along with the data collected as per IMO's DCS.…”
Section: Discussionmentioning
confidence: 99%